Study of the Reliability and Validity of Objective Structured Clinical Examination (OSCE) in the Assessment of Clinical Skills of Audiology Students - Nickbakht, Mansoureh (Glob J Health Sci, 2013)
INTRODUCTION: Audiology students should possess clinical competence and skills. To achieve this, their clinical skills must be properly assessed. The Objective Structured Clinical Examination (OSCE) is a standard and fair examination of clinical competence. The goal of this study is to devise a checklist of OSCE examination criteria and study their validity and reliability for assessing the clinical competence of Audiology students. METHODS: Among the various procedures in which audiology students should possess demonstrated competence, 10 specific skills were selected and checklists were prepared. Faculty members of university’s Audiology Department were consulted to determine the validity of the checklists. Subsequently, the examination was administered to all 14 fourth-year audiology students in their final semester of study at Ahvaz Jundishapur University of Medical Sciences. The examination consisted of three question stations and seven procedure stations. Each station was managed by two examiners who independently used a checklist to score each student’s performance in a given procedure. To determine reliability, the Spearman test was used. RESULTS: The correlation between each examiner’s scores of students at question stations was 0.908. The correlation between each examiner’s scores at procedure stations was 0.857 (p=0). The site of lesion test had the highest correlation (0.948) and immittance audiometry had the lowest correlation (0.585). CONCLUSION: The prepared checklists had good validity and reliability and can be used to evaluate the clinical competence of audiology students in their final semester of study.